Writing Through Children's Common Experiences (2016)
ABSTRACT: This research paper reports the impact that the collective creation of stories had on third grade students’ written production in English at Ferrini School, a private institution in Robledo neighborhood, Medellín, Colombia. In order to increase students written production, I proposed a set of actions that moved from writing aloud and shared and guided writing to independent writing. I also used observations that were recorded in my journal, an interview to the CT and students, and students’ production to appraise their perceptions about how the activities proposed had impacted their written productions. The analysis of the information revealed that the creation of collective stories had a positive effect on students as they progressed in the conventional use of the language, and wrote more structured stories. Their desire to use English in different moments of the class increased as well as their engagement in collaborative learning activities.